Faktor-Faktor Penyebab Anak Putus Sekolah Di Desa Cot Seumeureung Kecamatan Samatiga Kabupaten Aceh Barat - Rizki Duana; Sakdiyah Sakdiyah; Irsyadillah Irsyadillah (Jurnal Ilmiah Mahasiswa Pendidikan Ekonomi, 2019)
Dropout is one of the social conditions experienced by the people of Cot Seumeureung Village, Samatiga Subdistrict, almost every year found children who drop out of school with various factors that cause it so interesting to know what exactly causes the children in this village decided to quit school. The purpose of this study is to determine the factors that cause children drop out in the village of Cot Seumeureung Samatiga District West Aceh regency. This study used a qualitative approach, the type of research used is descriptive research. The subjects of this study are children dropping out of school in Cot Seumeureung Village as many as 17 people, the whole subject was made a respondent in this research. Data collection was done by interview, documentation, and observation technique. The type of interview selected is an in-depth interview. Data analysis technique used in this research is qualitative data analysis that is describing and interpreting data obtained in field from informant, with steps: data reduction, data presentation, conclusion and verification. The result of the research shows that the factors causing the drop out of school in Cot Seumeureung Village of Samatiga Subdistrict are five: family economic factor, lack of awareness and attention of parents of children education in Cot Seumeureung village, low interest of children for school caused by environment and friend Peers. Culture is the fourth factor, which is related to people's habits that leads their school-aged children to help earn a living, and the location or location of remote schools is the fifth factor that can lead to drop out of Cot Seumeureung Village school.